CRITICAL REVIEW OF ANESTHESIA TECHNICIAN CERTIFICATION REQUIREMENTS: ADDRESSING STANDARDS, COMPETENCIES, AND CREDENTIALING PROCESSES - 1Mohammed Saleh Mohammed Alrehan, 2Mohammed Zayed Dahin Alsinan, 3Dahin Zayed Dahin Alsinan, 4Ahmed Abdullah Saleh Alblowi, 5Abdulrahman Ahmad Khalid Mohammad, 6Raed Mohammed Abdullah Alyami, 7Ali Mana Nasser Alhutaylah, 8Hussain Mana Nasser Alhutaylah (Chelonian Research Foundation, 2022)
This critical review explores the existing anesthesia technician certification requirements, focusing on standards, competencies, and credentialing processes. This article recognizes the preferences and impediments of the current accreditation prepared by analyzing existing information and data. Fundamental discoveries highlight contrasts in competency appraisal approaches across districts, as well as contrasts in accreditation guidelines. The discuusion dives into suggestions for patient safety, staff advancement, and administration choices. Suggestions are advertised to progress the accreditation and prepare to advance value, brilliance, and responsibility in proficient anesthesiology. Keywords: Anesthesia technician, certification, standards, competencies, credentialing, patient safety